UJI INOKULAN MYCOSILVI DAN BAHAN AMELIORAN PADA Anthocephalus cadamba Miq DI TANAH BEKAS TAMBANG PASIR SILIKA - Putri Aurum; Sri Wilarso Budi; Prijanto Pamoengkas (PROSIDING SEMINAR NASIONAL CENDEKIAWAN, 2018)
Open mining  causes some environmental impacts such as declining levels of soil fertility, lowering soil pH, and increasing toxic acid mine waste such as Al, Fe, Cu, and Zn. Soil quality can be improved by the addition of soil ameliorant and MycoSilvi, an inoculum of arbuscular mycorrhizae enriched by mycorrhizal helper bacteria. The aim of this study is to analyze the growth response of Anthocephalus cadamba seedlings affected by the addition of soil ameliorant and Mycosilvi grown in soil media from silika sand post mining. The experimental design used in this study is completely randomized design with split pot design that consist of two treatment factors (Mycosilvi and soil ameliorant) with five replications. The main plot is Mycosilvi that consists of two levels (without Mycosilvi and with Mycosilvi). The subplot is soil ameliorant that consist of six levels (compost 0 g, lime 0 g; compost 0 g, lime 5.79 g; compost 0 g, lime 10.58 g; compost 35 g, lime 0 g; compost 35 g, lime 5.79 g; compost 35 g, lime 10.58 g). The interaction of Mycosilvi and soil ameliorant significantly increased height, diameter, biomass, and mycorhhizal colonization of A. cadamba. The Mycosilvi and soil ameliorant (35 g of compost and 10.58 g of lime) was the best treatment to increased height, diameter, biomass, and root shoot ratio of A. cadamba.